Expression of CD11b and CD18 on PMNs stimulated with IL-2 - Bahaa K.A. Abdel-Salam (Mediterranean Journal of Hematology and Infectious Diseases)
It has previously shown that normal human Polymorphonuclear neutrophils (PMNs) contain cytoplasmic stores of molecules associated with cell migration. CD11b and CD18 are the most important molecules involved in cell migration. These cytoplasmic molecules were found to translocate to the cell surface with different stimuli. In this study, IL-2 in vitro activation of PMNs had acquired integrins (CD11b and CD18) on the surface. Some studies had suggested that CD11b and CD18 expressed on the surface of neutrophils might be played a role in their migration.